2017 年世界统计手册 - United Nations Department of Economic; Social Affairs (United Nations, 2017)
The 2017 edition of the World Statistics Pocketbook is the forty-first in a series of annual compilations of over 50 key statistical indicators from more than 20 international statistical sources and are presented in one-page profiles for 30 world geographical regions and 232 countries or areas. Organised into five (5) sections – general information, economic indicators, major trading partners, social indicators, and environmental and infrastructure indicators. The indicators in the profiles cover the following topics: communication, crime, development assistance, education, energy, environment, finance, gender, health, international tourism, and science and technology, to name a few.